Primeiro inventário de emissões atmosféricas por veículos automotores leves: estudo de caso da contribuição da comunidade da Universidade Tecnológica Federal do Paraná câmpus Londrina - PR - Babinsk, Bruna Luiza (2017)
Between all the means of transportation, light vehicles have been the population greed’s target. The flexibility, comfort and practice from light vehicles became indispensable attractions for people who are looking agility of time and space. Despite, the use of light vehicles brings gas emissions that are pollutants for the environment and the living beings. Therefore, the present project shows the inventory of the trajectory of the Federal Technological University of Paraná Community, in Londrina. The fieldwork was realized by two ways, first in-person, during March 9th of 2017, and second in online network, during 45 days through institutional email and through a university group on a social network. The in-person fieldwork covered 7,59% of the UTFPR – LD Community and totaled 84 effectual answers. Beyond the fieldwork, 338 effectual registrations were arranged by the UTFPR – LD Department of General Services. The quantity of Non-methane hydrocarbon (NMHC), Carbon Monoxide (CO), Nitrogen Oxides (NOx) and Carbon Dioxide (CO2) emissions in g/km were calculated for each light vehicle, then were revealed the brands HYUNDAI, TOYOTA, CHEVROLET, NISSAN, VOLKSWAGEN, JEEP e RENAULT as the brands more responsible of atmosphere emissions. The emissions from those 84 answers in the first semester of 2017 totaled in 5,01 Kg of NMHC, 77,36 Kg of CO, 5,63 Kg of NOx and 23,42 tons of CO2. Finally, the Project motivates studies of social, environmental and economic improvements for the UTFPR - LD Community.